ANTESEDEN KEPUASAN KONSUMEN PADA SUPERMARKET BAHAN BANGUNAN MITRA 10, SIDOARJO - Desembrianita, Eva; R Sukatmadiredja, Noneng (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2019)
This research was conducted to analyzed the effect of independent variables consisting of service innovation, customer service and customer relationship management on the variables of customer satisfaction. This research is a survey research by distributing questionnaires with a nonprobability sampling design, to 96 respondents / consumers of Mitra 10, Sidoarjo. Data analysis technique uses multiple linear regression. The results showed that Fcount of 72.595 was greater than Ftable (72.595> 2.699). The t test on each variable gives the results of service innovation has a significant effect on consumer satisfaction because t table is 1,984, the value of t count in X1 is 5.614 (t count> t table). Customer service has a significant effect on consumer satisfaction because the tcount value at X2 is 2.834 (t count> t table). Customer Relationship Management (CRM) has a significant effect on consumer satisfaction because thitung in X3 is 3.817 (thitung> t table). Service Innovation variables have an effect of 18.4% on customer satisfaction, while Customer Service is 4.9% and Customer Relationship Management (CRM) is 9.5%. Of the three, service innovation is the dominant variable influencing consumer satisfaction Keywords: Service Innovation, Customer Service, Customer relationship Management, Customer Satisfaction